2002
DOI: 10.1046/j.1537-2995.2002.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of FFP photochemically treated with amotosalen (S‐59) and UV light compared to FFP in healthy volunteers anticoagulated with warfarin

Abstract: Study data of warfarin-treated healthy volunteers demonstrate that psoralen plus UV-treated FFP provides an equivalent in vivo coagulation response to control plasma. A 1-L dose of FFP in adults may provide an initial increment of 0.10 IU per mL of FVII. In the absence of bleeding, FVII levels return to baseline after 8 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 15 publications
5
68
0
Order By: Relevance
“…Comparable increases in factor VII levels and in factor VII incremental recovery were observed between the PCT-FFP and conventional FFP treatment groups. These findings are consistent with the pharmacokinetic study of factor VII in nonbleeding subjects 6 and indicate that PCT-FFP can be dosed similarly to C-FFP. In this study, factor VII dose, the PT response, and the change in factor VII levels were significantly correlated.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Comparable increases in factor VII levels and in factor VII incremental recovery were observed between the PCT-FFP and conventional FFP treatment groups. These findings are consistent with the pharmacokinetic study of factor VII in nonbleeding subjects 6 and indicate that PCT-FFP can be dosed similarly to C-FFP. In this study, factor VII dose, the PT response, and the change in factor VII levels were significantly correlated.…”
Section: Discussionsupporting
confidence: 86%
“…4,23,24 A controlled, randomized, crossover study in healthy subjects treated with warfarin demonstrated that PCT-FFP provided an equivalent in vivo response to C-FFP, as assessed through postinfusion kinetics of factor VII and recovery of factors II, VII, IX, and X. 6 A single-arm, open-label study in patients with congenital factor deficiencies (I, II, V, VII, X, XI, XIII, and protein C) demonstrated posttransfusion recoveries and support of hemostasis during invasive procedures comparable to that observed with C-FFP. 5 The current study demonstrated no difference in correction of the PT or PTT on a dose-and weight-adjusted basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a pharmacokinetic study of FFP (~12 mL/kg) administered to warfarin-treated participants [33], the effect of plasma on both factor VII levels and PT measurements peaked at 15 minutes and persisted only for 8 hours. Warfarin rebound effect occurred in all participants by 12 hours and required oral vitamin K for definitive correction.…”
Section: Discussionmentioning
confidence: 99%
“…Upon exposure to UVA light, Amotosalem becomes reactive and forms a chemical crosslink that locks-up the strands of RNA and DNA, blocking and inactivating the replication of viruses, bacteria and leukocytes in PLT concentrates (25)(26)(27)(28).…”
Section: List Of Abbreviationsmentioning
confidence: 99%